Ultra-sensitive and highly selective H2sensors based on FSP-made Rh-substituted SnO2sensing films - K. Inyawilert (2018)
© 2016 Elsevier B.V. In this research, SnO2nanoparticles doped with 0.1–2 wt% rhodium (Rh) were synthesized by flame spray pyrolysis and systematically investigated for H2-sensing applications. From X-ray and electron microscopic characterizations, SnO2nanostructures exhibited spheroidal morphology with polycrystalline tetragonal SnO2phase and Rh might form solid solution with SnO2lattice. The sensing films were prepared by spin coating technique and their gas-sensing performances were studied at the operating temperatures ranging from 100 to 350 °C in dry air. Gas-sensing measurements showed that SnO2sensing films with the optimal Rh-doping level of 0.2 wt% exhibited an ultra-high response of ∼22,170, which was more than three orders of magnitude higher than that of undoped one, and a short response time of 6 s towards 30,000 ppm H2at an optimum operating temperature of 300 °C. In addition, the optimal Rh-doped SnO2sensor displayed high H2selectivity against NO2, SO2, C2H4, C3H6O, CH4, H2S and CO. Thus, Rh-doped SnO2nanoparticulate thick films are promising candidates for H2-sensing applications.